2008
DOI: 10.1097/jcp.0b013e31817e0ecb
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibiting Antidepressants Are Associated With an Increased Risk of Nonvertebral Fractures

Abstract: Not only users of TCAs but also of SSRIs have a significantly increased risk of nonvertebral fractures, in SSRI users especially after prolonged use. Despite fewer early adverse effects of SSRIs, physicians treating elderly depressive patients should be aware of the unfavorable long-term consequence of SSRIs on fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 47 publications
0
135
1
3
Order By: Relevance
“…54,55 This association was first observed in a series of case-control studies using large administrative databases [54][55][56] but has since been replicated with prospective cohort studies. 57,58 In a multivariate analysis, controlling for such factors as depressive symptoms, falls history, visual and cognitive impairment, comorbidities, postural hypotension, other medications, alcohol and smoking, the risk of fragility fracture over 8 years with current SSRI use was found to be 2.35 (1.3-4.2). 57 SSRIs also have been found to have a dose relationship with fractures.…”
Section: Depression Antidepressants and Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 This association was first observed in a series of case-control studies using large administrative databases [54][55][56] but has since been replicated with prospective cohort studies. 57,58 In a multivariate analysis, controlling for such factors as depressive symptoms, falls history, visual and cognitive impairment, comorbidities, postural hypotension, other medications, alcohol and smoking, the risk of fragility fracture over 8 years with current SSRI use was found to be 2.35 (1.3-4.2). 57 SSRIs also have been found to have a dose relationship with fractures.…”
Section: Depression Antidepressants and Fracturesmentioning
confidence: 99%
“…57,58 In a multivariate analysis, controlling for such factors as depressive symptoms, falls history, visual and cognitive impairment, comorbidities, postural hypotension, other medications, alcohol and smoking, the risk of fragility fracture over 8 years with current SSRI use was found to be 2.35 (1.3-4.2). 57 SSRIs also have been found to have a dose relationship with fractures. 54,58 Similar to the risk for falls, the risk of fracture associated with SSRI use is the highest in the first 2 weeks of treatment (OR: 6.30; CI: 2.65-14.97) but remains elevated with continuous antidepressant use beyond the first month of use (OR: 1.32; CI: 1.19-1.48).…”
Section: Depression Antidepressants and Fracturesmentioning
confidence: 99%
“…Comme tout bon médicament, les ISRS ne sont pas dépourvus d'effets secondaires. L'un d'entre eux est de provoquer une perte osseuse chez les patients traités au long cours, l'autre est d'augmenter l'appétit [16][17][18][19]. Ces observations cliniques suggèrent que la sérotonine d'origine cérébrale pouvait bien être un régulateur de la masse osseuse et de l'appétit.…”
Section: La Leptine Inhibe La Sérotonine Cérébraleunclassified
“…Ziere et al [2] reported that SSRIs and tricyclic antidepressants (TSAs) can cause fractures, especially in the bones of older patients, and fractures have appeared in the vertebrae of patients using SSRIs for long periods but not with TSAs.…”
Section: Dear Editormentioning
confidence: 99%